2021
DOI: 10.31389/jltc.76
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of COVID-19 on Unpaid Carers of Adults with Long-Term Care Needs and Measures to Address these Impacts: A Rapid Review of Evidence up to November 2020

Abstract: Context: Unpaid carers are the backbone of long-term care (LTC) systems around the world. The COVID-19 pandemic has further increased the pressure many unpaid carers experience; however, their experience has been largely absent from public reporting. Objective: We aim to map the available evidence of the impacts of COVID-19 on unpaid carers of adults (>18 years) with LTC needs as well as of measures implemented to mitigate these effects and how well they have worked. Method: We conducted a rapid review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 19 publications
(30 reference statements)
4
44
0
Order By: Relevance
“…This adverse trend, according to the observations conducted thus far, has become a common experience of informal carers around the world, regardless of the care system operating in a given country [ 1 , 19 , 22 , 35 , 47 , 54 ]. Pandemic-related changes in the caring responsibilities have lowered informal carers’ overall well-being, both mental and physical [ 33 ], causing symptoms such as sleep disturbances, anxiety or depression [ 55 ]. Moreover, it has increased the risk of carer burnout [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This adverse trend, according to the observations conducted thus far, has become a common experience of informal carers around the world, regardless of the care system operating in a given country [ 1 , 19 , 22 , 35 , 47 , 54 ]. Pandemic-related changes in the caring responsibilities have lowered informal carers’ overall well-being, both mental and physical [ 33 ], causing symptoms such as sleep disturbances, anxiety or depression [ 55 ]. Moreover, it has increased the risk of carer burnout [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reported lower wellbeing, financial difficulties such as greater reliance on foodbanks, and lack of respite opportunities. 124,125,126,127,128 Carers are more likely to have poor health with over 60% of people providing over 20 hours of care a week having two or more long-term conditions. During the pandemic, over 20% have been waiting for NHS treatment.…”
Section: Unpaid Carersmentioning
confidence: 99%
“…The pandemic is also having a negative impact on the mental and physical wellbeing of family carers (see Preventing Well, Table 2), many of whom are unpaid and have experienced changes in care responsibilities (increased care hours) with financial implications, suggesting that financial assistance is a potential source of support. 49 Studies and reports of home care services found that increased levels of carer stress could be mitigated by visiting care workers 112,110 although family carers were often concerned about staff availability and potential risk of infection, so sometimes did not continue with such services. 142,113,17 Other family carers also worried whether home care services would be available in future if they refused them, 142 Studies that explored the use of remote communication technologies at home found that a substantial proportion of people living with dementia were unable to access remote consultations, possibly related to lack of access, knowledge or confidence to use the technology.…”
Section: T a B L Ementioning
confidence: 99%